Keeping Good Sensing Performance of Metal–Dielectric–Metal Waveguides After Coating Treatment - Zhihui He; Mingzhuo Zhao; Zhiquan Chen; Hui Xu; Mingfei Zheng; Hongjian Li (IEEE Photonics Journal, 2017)
Good sensing performance is observed in metal–dielectric–metal (MDM) waveguides in recent research. However, Ag will be oxidized in air. The oxidization layer makes the sensing performance not as high as before. Plating an SiO2 film on the surface of the Ag waveguide not only can avoid oxidization but can keep good sensing performance through our numerical discussion as well. The decaying rate of electric field E at the interface and inside is also defined to illustrate the phenomenon mentioned above. We hope our findings will provide guidance for the integrated plasmonic devices.